PENGARUH KOMPENSASI, KEDISIPLINAN, JENJANG KARIR, DENGAN MODERASI LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN RS MUHAMMADIYAH TUBAN - Yenie Surveyanti; Dasrun Hidayat; Yani Restiani Widjaja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Employee productivity is a vital element for achieving optimal organizational performance, particularly in the healthcare sector, which demands excellent patient care. Muhammadiyah Tuban Hospital (RSMT) faces several productivity challenges, evident in ongoing complaints about the competence and behavior of healthcare workers, the ineffective implementation of incentive programs, and inadequate workloads. These internal challenges are reinforced by survey results indicating suboptimal employee job satisfaction and a Bed Occupancy Rate (BOR) of 2024 that remains below operational standards. Performance evaluations also reveal that a number of staff, both medical and non-medical, have not met expectations in key aspects such as satisfaction, loyalty, and work behavior. Previous research consistently demonstrates that compensation, discipline, career progression, and the work environment are important factors influencing performance. Compensation enhances motivation and retention; discipline reflects organizational ethics; career progression encourages work continuity; and the work environment supports task effectiveness. However, the specific influence of these four factors on staff productivity at RSMT has never been comprehensively studied. Therefore, this study aims to analyze the influence of compensation, discipline, career path, and work environment on employee productivity at RSMT. The analysis results show that the influence of these variables varies. Only discipline and career path significantly influence productivity. Meanwhile, recovery and work environment variables do not have a significant impact. These findings are expected to provide key input for hospital HR management policies to improve service quality, strengthen institutional performance, and balance ongoing technological developments.